The efficacy of homestyle rehabilitation on negative symptoms in chronic schizophrenia: A randomized controlled trial - Chai, Jiabao; Liu, Fuquan; Liu, Lin; Hu, Na; Huang, Wenqian; Wang, Hong; Cui, Yonghua; Liu, Hongyan; Li, Xiaojun; Li, Ying (Frontiers in Psychiatry, 2023)
Objective: Schizophrenia is a debilitating mental disorder with a high disability rate that is characterized by negative symptoms such as apathy, hyperactivity, and anhedonia that can make daily life challenging and impair social functioning. In this study, we aim to investigate the effectiveness of homestyle rehabilitation in mitigating these negative symptoms and associated factors. Methods: A randomized controlled trial was conducted to compare the efficacy of hospital rehabilitation and homestyle rehabilitation for negative symptoms in 100 individuals diagnosed with schizophrenia. The participants were divided randomly into two groups, each persisting for three months. The primary outcome measures were the Scale for Assessment of Negative Symptoms (SANS) and Global Assessment of Functioning (GAF). The secondary outcome measures included the Positive Symptom Assessment Scale (SAPS), Calgary Schizophrenia Depression Scale (CDSS), Simpson-Angus Scale (SAS), and Abnormal Involuntary Movement Scale (AIMS). The trial aimed to compare the effectiveness of the two rehabilitation methods. Results: Homestyle rehabilitation for negative symptoms was found to be more effective than hospital rehabilitation, according to the changes in SANS (T = 2.07, p = 0.04). Further analysis using multiple regression indicated that improvements in depressive symptoms (T = 6.88, p < 0.001) and involuntary motor symptoms (T = 2.75, p = 0.007) were associated with a reduction in negative symptoms. Conclusion: Homestyle rehabilitation may have greater potential than hospital rehabilitation in improving negative symptoms, making it an effective rehabilitation model. Further research is necessary to investigate factors such as depressive symptoms and involuntary motor symptoms, which may be associated with the improvement of negative symptoms. Additionally, more attention should be given to addressing secondary negative symptoms in rehabilitation interventions.